The Solvability of the Cancer Invasion System with the EMT and MET Processes - Mani, V.N. Deiva; Anthoni, S. Marshal (Discontinuity, Nonlinearity, and Complexity, 2026)
This work deals with the existence of the system consists of coupling dynamics of the two types of tumor cells among the density of epithelial cells (ECs) and the mesenchymal cells (MCs) with the proteins matrix metalloproteinases (MMPs) and extra cellular matrix (ECM) which involved in the invasion and the intravasation processes. Along with square integrable mesenchymal epithelial transition function, the existence and uniqueness of mathematical model illustrated under Faedo-Galerkin approximation method which governed by the invasion model along with EMT and MET process which contains nonlinear terms due to acidification and interactions.